IMPLIKASI RELASI SEKOLAH TINGGI TEOLOGI ARASTAMAR BENGKULU BAGI PENGEMBANGAN PELAYANAN MISI GEREJA KRISTEN INJILI DI INDONESIA JEMAAT KOTA BENGKULU - Made Nopen Supriadi (Jurnal PKM Setiadharma, 2020)
This paper is entitled "Implications of the Relationship between Arastamar Bengkulu College of Theology for the Development of Missionary Services for the Evangelical Christian Church in Indonesia, the City of Bengkulu Congregation." The facts show that not necessarily a graduate of the Theological College can be accepted into a church. This condition is shown by the lack of support from the Church to an Theological College and Theological College does not give graduates to a church. Despite these facts, the author sees different facts between the Arastamar Bengkulu Theological Seminary (STTAB) and the Evangelical Christian Church in Indonesia (GEKISIA) Bengkulu City. The author obtained data that there are many developments specifically in mission services since the arrival of STTAB and collaborating with GEKISIA, Bengkulu City. This development is very important for the writer to research and describe in scientific work. From the observation, it shows that the development of mission services in GEKISIA, Bengkulu City occurs because of the large use of mission personnel from STTAB graduates. Pioneering Evangelical Service Posts (PI) increased to 6 PI Posts. This development needs to be studied theoretically so that through writing it can contribute to the development of missionary services in the Church and other Christian institutions, and revitalize the relationship between Theological College and the Church.